2020
DOI: 10.3390/cancers12092445
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effects of Preventive Nutrition Supplement on Anticancer Radiotherapy in Lung Cancer Bearing Mice

Abstract: (1) Background: Radiotherapy (RT) is one of the major treatments for non-small cell lung cancer, but RT-associated toxicities usually impede its anticancer effect. Nutrient supplementation has been applied for cancer prevention or a complementary measure to anticancer therapy. Here, we explored the influence of total nutrition supplementation before and after cancer occurrence on the anticancer benefit and side effects of RT. (2) Methods: C57BL/6JNarl mice were inoculated with Lewis lung carcinoma cells and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The inhibition of GRP78 and YAP/TAZ by the Se-Y and FO combination suggested its potential radiosensitizing effect in these treated A549 sphere cells. In accordance with this, the nutrition supplement containing Se-Y, EPA, and DHA enhanced the anticancer effects of radiotherapy on lung cancer-bearing mice [ 61 ]. The GRP78-suppressing effects of the Se-Y and FO combination in previous studies [ 16 , 21 ] and this study also suggested the potential clinical impact of this nutrient combination in lung cancer therapy.…”
Section: Discussionmentioning
confidence: 84%
“…The inhibition of GRP78 and YAP/TAZ by the Se-Y and FO combination suggested its potential radiosensitizing effect in these treated A549 sphere cells. In accordance with this, the nutrition supplement containing Se-Y, EPA, and DHA enhanced the anticancer effects of radiotherapy on lung cancer-bearing mice [ 61 ]. The GRP78-suppressing effects of the Se-Y and FO combination in previous studies [ 16 , 21 ] and this study also suggested the potential clinical impact of this nutrient combination in lung cancer therapy.…”
Section: Discussionmentioning
confidence: 84%
“…Meanwhile, it is supposed that Se and FO are the critical components of the formula for anti-cancer efficacy. The commercial formula also enhanced the anticancer effects of radiotherapy by decreasing lung metastasis and EGFR expression and increasing apoptosis in LLC1 tumor-bearing mice [25,26]. On the other hand, a previous study has demonstrated that Se/FO can enhance the anticancer activity of bevacizumab by inhibiting tumor EGFR, TβR, and AXL proteins in breast tumor-bearing mice [27].…”
Section: Introductionmentioning
confidence: 95%
“…In this setting of improving fitness before treatments, Yu-Ming Liu et al [ 2 ] provided evidence in an animal model that nutrient supplementation by TNuF, a total nutritional formula, enhanced the anticancer effect of RT against lung cancer and metastasis in mice; the supplementation also reduced the wasting of sartorius muscle, underlying the need to take into account sarcopenia in clinical settings. Interestingly, the authors also showed that this strategy enhanced the anti-cancer immunity of RT, and therefore could sensitize to an anti-PD-1 immune treatment.…”
mentioning
confidence: 99%